The stress hormone norepinephrine increases the growth and virulence of Aeromonas hydrophila - Jinwei Gao; Bingwen Xi; Kai Chen; Rui Song; Ting Qin; Jun Xie; Liangkun Pan (MicrobiologyOpen, 2019)
Abstract Stress is an important contributing factor in the outbreak of infectious fish diseases. To comprehensively understand the impact of catecholamine stress hormone norepinephrine (NE) on the pathogenicity of Aeromonas hydrophila, we assessed variations in bacterial growth, virulence‐related genes expression and virulence factors activity after NE addition in serum‐SAPI medium. Further, we assessed the effects of NE on A. hydrophila virulence in vivo by challenging fish with pathogenic strain AH196 and following with or without NE injection. The NE‐associated stimulation of A. hydrophila strain growth was not linear‐dose‐dependent, and only 100 μM, or higher concentrations, could stimulate growth. Real‐time PCR analyses revealed that NE notably changed 13 out of the 16 virulence‐associated genes (e.g. ompW, ahp, aha, ela, ahyR, ompA, and fur) expression, which were all significantly upregulated in A. hydrophila AH196 (p < 0.01). NE could enhance the protease activity, but not affect the lipase activity, hemolysis, and motility. Further, the mortality of crucian carp challenged with A. hydrophila AH196 was significantly higher in the group treated with NE (p < 0.01). Collectively, our results showed that NE enhanced the growth and virulence of pathogenic bacterium A. hydrophila.